2021
DOI: 10.1021/acsomega.0c06009
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Silver Nanoparticles Using theLotus lalambensisAqueous Leaf Extract and Their Anti-Candidal Activity against Oral Candidiasis

Abstract: Oral candidiasis is widely spread in both humans and animals, which is caused mainly by Candida albicans. In this study, we aimed to biosynthesize silver nanoparticles (AgNPs) for the first time using the Lotus lalambensis Schweinf leaf extract (L-AgNPs) and investigated their anti-candidal potency alone or in combination with the leaf extract of L. lalambensis (L-AgNPs/LL) against C. albicans. The biosynthesized L-AgNPs were characterized by imaging (transmission electron microscopy, TEM), UV−vis spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 84 publications
0
36
0
1
Order By: Relevance
“…Our in vitro data showed no cytotoxicity of AgNPs up to a concentration of 100 ug/mL. In consistent, AgNPs showed no toxicity on human-adipose-derived stem cells [ 81 ] and the MCF-7 cell line [ 26 ]. However, the in vitro toxicity of AgNPs varies from one study to the other based on many factors, including manufacturing methods, size distributions, the cell line used, and culture conditions [ 82 ].…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Our in vitro data showed no cytotoxicity of AgNPs up to a concentration of 100 ug/mL. In consistent, AgNPs showed no toxicity on human-adipose-derived stem cells [ 81 ] and the MCF-7 cell line [ 26 ]. However, the in vitro toxicity of AgNPs varies from one study to the other based on many factors, including manufacturing methods, size distributions, the cell line used, and culture conditions [ 82 ].…”
Section: Discussionmentioning
confidence: 74%
“…Several studies have reported the anti-biofilm activity of biosynthesized AgNPs by a decrease in their biomass and complex and formation of a vesicle transit station which play a major role in the hyphal morphogenesis [ 78 , 79 ]. In this context, we previously showed that biosynthesized AgNPs using different plant extracts display powerful antibiofilm action against C. albicans [ 25 , 26 ]. Similarly, [ 80 ] showed that AgNP-treated C. albicans biofilm have no true hyphae, and there was a clear reduction in the number of cells, and disruption of the cell wall was also observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These particles also showed potential anti-bacterial activity toward S. pyogenes (ZOI = 14 ± 0.4 mm), S. aureus (ZOI = 16 ± 0.1 mm), B. subtilis (ZOI = 15 ± 0.3 mm), P. aeruginosa (ZOI = 21 ± 0.5 mm), S. typhi (ZOI = 19 ± 0.4 mm), and E. coli (ZOI = 17 ± 0.1 mm) [202]. In another study, Abdallah, Basem M., et al aimed to produce silver nanoparticles from Lotus lalambensis aqueous leaf extract and their anticandidal activity toward C. albicans (MIC = 125 µg/mL) [203]. Spherical silver nanoparticles were produced utilizing Symplocos racemosa.…”
Section: Synthesis Of Silver Nanoparticles Using Leaf Extracts: (2019-2020)mentioning
confidence: 99%
“…Leaves being a major source of the plants biological process were explored vastly for nanoparticle synthesis. e leaves of Lotus lalambensis and AgNPs synthesized have shown protective effect against oral candidiasis [14]. e synthesis of AgNPs from leaf extracts of Semecarpus anacardium, Glochidion lanceolarium, and Bridelia retusa has shown antibacterial and antibiofilm activity against human pathogens.…”
Section: Introductionmentioning
confidence: 99%